Scripture and Its Interpretation: A Global, Ecumenical Introduction to the Bible - Gorman, Michael J. (Baker Academic, 2017)
Top-notch biblical scholars from around the world and from various Christian traditions offer a fulsome yet readable introduction to the Bible and its interpretation.